2009
DOI: 10.1021/jm801533x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Homology Modeling of G-Protein-Coupled Receptors in Light of the A2A Adenosine Receptor Crystallographic Structure

Abstract: Homology modeling of the human A2A adenosine receptor (AR) based on bovine rhodopsin predicted a protein structure that was very similar to the recently determined crystallographic structure. The inaccuracy of previous antagonist docking is related to the loop structure of rhodopsin being carried over to the model of the A2A AR and was rectified when the β2-adrenergic receptor was used as a template is used for homology modeling. Docking of the triazolotriazine antagonist ligand ZM241385 1 was greatly improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 37 publications
11
103
0
Order By: Relevance
“…Mutation of Ser277 7.42 , Thr88 3.36 ,and Leu85 3.33 to alanine abrogated this agonist interaction and reduced the potency and affinity of CGS21680 by at least 100-fold in agreement with previous studies (Kim et al, 1995;Gao et al, 2000;Ivanov et al, 2009). In contrast, the potency and affinity of LUF5834 were unaffected by the mutation of either Ser277 7.42 or Thr88 3.36 to alanine.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Mutation of Ser277 7.42 , Thr88 3.36 ,and Leu85 3.33 to alanine abrogated this agonist interaction and reduced the potency and affinity of CGS21680 by at least 100-fold in agreement with previous studies (Kim et al, 1995;Gao et al, 2000;Ivanov et al, 2009). In contrast, the potency and affinity of LUF5834 were unaffected by the mutation of either Ser277 7.42 or Thr88 3.36 to alanine.…”
Section: Discussionsupporting
confidence: 90%
“…As a partial agonist, LUF5834 will bind with a similar affinity to this mutated receptor, although a loss of efficacy will be observed (Christopoulos and Kenakin, 2002). Glu169 5.30 in ECL2 was highlighted as having a key role in ligand binding by ligand docking, mutagenesis studies, and finally the antagonist-bound crystal structure Jaakola et al, 2008;Ivanov et al, 2009). Consistent with these observations, we observed a Ͼ20-fold reduction in the affinity of [ 3 H]ZM241385.…”
Section: Nonribose Agonist For Adenosine Receptors 485supporting
confidence: 82%
See 1 more Smart Citation
“…The majority of models had root-mean-square deviation values of more than 10 Å for the ligand binding site, and only one predicted the typical perpendicular orientation of ZM241385 halfway the extracellular and transmembrane domains. The reasons for this generally large divergence were implicitly examined by Ivanov et al (2009). The authors noted that domain knowledge such as mutagenesis data yielded useful constraints when docking ZM241385 into a receptor homology model.…”
Section: E Receptor Structure and Receptor Homology Modelingmentioning
confidence: 99%
“…at ASPET Journals on May 11, 2018 molpharm.aspetjournals.org rically opposed modes of ligand binding for the same receptor-ligand complex), there were examples of well supported modeling that was later validated crystallographically (among others, see Ivanov et al, 2009;Michino et al, 2009;Kufareva et al, 2011). Comparisons of crystal structures and homology models revealed that, for some GPCRs, reasonably accurate receptor-ligand complexes can be constructed through homology modeling followed by molecular docking (Costanzi, 2008(Costanzi, , 2010(Costanzi, , 2012Reynolds et al, 2009).…”
Section: Drug Design From Gpcr Crystallographic Structures 367mentioning
confidence: 99%